2020
DOI: 10.31557/apjcp.2020.21.12.3711
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genetic Polymorphisms of N-acetyltransferase 2 and Relation with Chronic Myeloid Leukemia

Abstract: Objectives: The N-Acetyltransferase 2 (NAT2) gene encodes a key enzyme involved in xenobiotic metabolism, which contributes to the detoxification of numerous cancer therapy-induced products. However, the NAT2 genotype/phenotype is not fully understood and few studies have reported its relationship with CML. The aim of this study was to determine whether its polymorphisms ( C481T, G590A, 803A>G and 857G>A ) have a role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…and in turn reduce the mortality rate of the disease. For this reason, recent studies have been instigated in Sudan regarding CML patients, to ascertain how susceptibility to the disease is affected by polymorphism of certain genes such as xenobiotic ones [4][5][6] and BCR-ABL kinase gene as in this study. The Ph (Philadelphia) chromosome is considered a cytogenetic hallmark of CML, as it occurs in 90-95% of patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…and in turn reduce the mortality rate of the disease. For this reason, recent studies have been instigated in Sudan regarding CML patients, to ascertain how susceptibility to the disease is affected by polymorphism of certain genes such as xenobiotic ones [4][5][6] and BCR-ABL kinase gene as in this study. The Ph (Philadelphia) chromosome is considered a cytogenetic hallmark of CML, as it occurs in 90-95% of patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…Few other studies have also examined the relationship between MTRR 66 AG polymorphism and cancer risk. These studies found a significant association between a decreased risk of acute lymphoblastic leukemia and an augmented risk for hepatocellular carcinoma [ 32 , 33 , 34 , 35 , 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…In this case, chromosomal translocation results in an oncogenic BCR-ABL gene fusion that increases tyrosine kinase (TK) activity. Kinases that are abnormally activated disrupt downstream signaling pathways, resulting in abnormal cell proliferation, differentiation, and resistance to cell Genetic Polymorphisms of Xenobiotics-Metabolizing Enzymes Contributing to Leukemia DOI: http://dx.doi.org/10.5772/intechopen.107324 death [43]. Joshi et al reported the CYP2C19 gene polymorphisms in susceptibility to CML.…”
Section: Phase 1 Genetic Polymorphisms Most Frequently Associated Wit...mentioning
confidence: 99%
“…A meta-analysis by Jiang et al investigated the relationship between NAT2 polymorphisms and onset risk of acute leukemia and reported there is no significant difference found between the fast-acetylator incidence of NAT2 haplotype and the onset risk of acute lymphoblastic leukemia (ALL, OR = 0.70, 95% CI = 0.45-1.08) or AML, OR = 0.79, 95% CI = 0.46-1.47) [52]. No significant difference was found in NAT2 fast and slow acetylator frequencies between CML patients and controls [47], while Tebien et al revealed the protective effect of NAT2A 803G and G857A against CML [43].…”
Section: Phase 11 Genetic Polymorphisms Most Frequently Associated Wi...mentioning
confidence: 99%